Speech Act Strategies of Prospective Indonesian Language Teacher Students in Academic Presentations: a Pragmatic Perspective - Wahyuni, Wika; Sudika, I Nyoman; Susanti, Pipit Aprilia; Pratama, Januari Rizki (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Public speaking is a crucial skill for students, especially prospective teachers, who serve as primary communicators in the learning process. However, numerous studies have shown that prospective teachers still face a variety of challenges in public communication, particularly in digital-based academic presentations, including linguistic, psychological, technical, material mastery, body language, environmental, and visual aid use. Therefore, this study aims to describe students' speaking strategies in academic presentations from a pragmatic perspective. This study uses a qualitative approach with observation and interviews with students of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, University of Mataram. Data in the form of students' oral utterances during academic presentations were analyzed using speech act theory to identify the types and pragmatic functions of the speaking strategies used. The results of the study indicate that students utilize various speaking strategies through assertive, directive, expressive, and commissive speech acts. Assertive speech acts are used to convey academic material, directive speech acts function to direct the audience's attention, while expressive and commissive speech acts are used to maintain politeness, manage awkwardness, and respond to academic pressure during presentations. These findings indicate that students' speaking strategies serve as pragmatic mechanisms in managing obstacles to public communication, while also being an important provision in developing the professional competence of prospective teacher students in the digital era.